DESIGN APPLICATION MOBILE MANAGEMENT STOCK OF ITEMS BASED ON ANDROID AT WARDIM SHOP, GOWA DISTRICT - Rayhan, Rahmat; Haripuddin, Haripuddin; Sa'ban Miru, Alimuddin (Fakultas Teknik Universitas Negeri Makassar, 2024)
The purpose of this study is to design an Android-based stock management mobile application and to find out the results of testing the Android-based stock management application. This application uses the type of research is Research and Development (R&D), which is a process or step to develop a new product or improve an existing product. This study was conducted to create a stock management application that can help store employees in stocking goods. The results of this study produce a product in the form of a stock management application that can make it easier for store employees to get stock information. This research was conducted at Wardim Store. The research data was obtained by administering questionnaires, interviews and documentation. This system was tested using ISO 25010 with 4 characteristics, namely functional suitability, portability, usability, and performance efficiency. Functional suitability testing was carried out by two expert lecturers as system validators and it was found that this application was suitable for use. Portability testing was carried out by observing the output results produced using Android smartphones in various versions, the results obtained showed that this stock management application system ran well on several versions of Android. Usability testing carried out by store employees was in the Very Good category. Performance efficiency testing is done using APPTIM by measuring real-time data for the CPU used, which is 100%, 287 Mb memory when the application is used. The developed stock management application can be used by employees at Wardim Store.